THE ROLE OF MUHAMMAD KASHGIRI’S “MUNYATUL MUSOLLI AND GUNYATUL MUBTADI” IN THE HANAFI SECT - Karimova Muyassarkhon Abdukayumovna; Gofforov Zafariddin Zaynobiddinovich (Galaxy International Interdisciplinary Research Journal, 2023)
In this article, the life of Abu Abdullah Sadiduddin Muhammad ibn Ali al-Kashgari, as well as his activities in fiqh, nahw, dictionary, tafsir and syrat, Imam Kashgari’s book "Minyatul Musolli wa Gunyatul Mubtadi" and the texts of the school of fiqh of the Hanafi school of jurisprudence. it is said that it is one of the enriched works and that Shaykh Ibrihim al-Halabi left two commentaries on the text of "Munyat ul-Musoli".